Piled Raft over Soft Marine Clay: Comparison of In-situ Measurement and Numerical Analyses - Azhari, Azlina (2011)
Geotechnical works in deep deposit of highly compressible soft clay is always associated with excessive differential settlement. The site evaluation and settlement analysis had been performed on five cylindrical steel tanks situated at Pasir Gudang, Johor in which all of the tanks are currently in service for fuel oil storage. This paper will describes the methodology of geotechnical study and engineering analysis for constructing large scale steel tanks founded on piled raft over compressible soil layers. Discussion on the design method, engineering consideration and hydrostatic test of the cylindrical steel tanks were presented in subsequent sections. Hydrostatic test was conducted to verify the foundation adequacy of the steel tanks constructed on piled raft foundation and to minimize the post construction settlement of the tank to an acceptable limit. Hydrostatic test was carried out by gradually fill up the tank with water until full load, retain for few days and gradually empty the tank. The hydrostatic test data was used to assess the magnitude of displacement (settlement and heave) of the tanks. Forward analyses which predict the magnitude and pattern of settlement were also presented. The estimated and measured settlement had been compared, in which analysis by using all three methods gave good settlement prediction to the actual value. The controlling factors which contribute to various displacement profiles of the tanks, namely subsoil profile, pile termination condition and sea water tide were also discussed.